Evaluating the Causality Effect of Exchange Rate and Nigeria Balance of Payment: An Empirical Analysis (Journal of Management and Social Sciences, 2017)
AbstractA country’s exchange rate and balance of payment are usually regarded as one of the indicator by which a nation’s strength can be measured especially its economic strength. Exchange rate plays a major role in international trade because no nation can remain in autarky due to varying factor endowments. Nigerian economy experienced chronic deficit on the balance of payment account, fall in the price of Naira and grossdomestic product growth rate due to over-dependency on imported products, reliance of revenues from oil exports, massive imports of refined petroleum, and other related products. The study evaluates the causality effect of foreign exchange rate and Nigeria balance of payment between the periods of 1970 and 2015. The data obtained were subjected to VECM Granger Causality method of analysis. The results revealed thatexchange rate and balance of payment granger cause each other at 5% level of significance. The study recommended that there should be a restriction on trade openness of goods or services that can be produced locally and diversification of Nigerian economy by the economy managers. The study concluded that there is high propensity for Nigerian economy to achieve favourable balance of payment, if the above recommendations are implemented.